Internal validity evidence of a knowledge questionnaire on alcohol use, abuse and dependence and associated questions - Divane de Vargas; Dionasson Altivo Marques; Rosa Jacinto Volpato; Erika Gisseth Leon Ramirez; Maria do Perpétuo Socorro de Sousa Nobrega (Associação Brasileira de Enfermagem, 2023)
ABSTRACT Objectives: to perform content validity and verify the psychometric properties of the adapted version of an alcohol knowledge questionnaire and associated questions. Methods: a methodological study, in which a committee of judges analyzed the questionnaire item representativeness, clarity and relevance. Item response theory was used to assess the instrument psychometric properties applied to a sample of 240 health professionals. Results: the questions were adjusted according to judges' assessment, obtaining a satisfactory Content Validity Index (0.98). High discrimination ability and adequate difficulty levels were observed in 75% of multiple-choice questions and in 25% of statements. Conclusions: the instrument presented content validity with satisfactory indices. However, it is recommended that the questionnaire adapted in this study be used in different samples of health professionals from other parts of Brazil, in order to provide greater robustness to its reliability.